2021
DOI: 10.3390/ijerph18041899
|View full text |Cite
|
Sign up to set email alerts
|

The Experiences of Grief and Personal Growth in University Students: A Qualitative Study

Abstract: Background: Experiencing the death of a close person, especially in emerging adults and students, can have profound effects on the bereaved individual’s life. As most research in this field has focused on negative effects of a loss, little is known about potential positive effects experienced by bereaved university students. This study investigated the experience of grief and personal growth in a sample of students from The University of Melbourne, Australia. Methods: Semi-structured interviews via Zoom/teleph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 61 publications
(103 reference statements)
0
10
0
2
Order By: Relevance
“…PTG enables individuals to reframe their experiences and perceive potential benefits from life trauma, resulting in improving their relationships with others, creating new possibilities, advancing personal strength, bringing spiritual change, or increasing the appreciation of life (Jin et al, 2014 ). Previous studies have found that PTG may occur in various people who have experienced trauma, such as bereavement (Tan and Andriessen, 2021 ), HIV infection (Ye et al, 2018 ), combat (Marotta-Walters et al, 2015 ), earthquake (Ma et al, 2019 ), and other life-changing events. Studies on patient care indicated that the level of PTG was negatively associated with depressive effect (Siegel et al, 2005 ), emotional distress (Urcuyo et al, 2005 ), and positively associated with quality of life (Xiong et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…PTG enables individuals to reframe their experiences and perceive potential benefits from life trauma, resulting in improving their relationships with others, creating new possibilities, advancing personal strength, bringing spiritual change, or increasing the appreciation of life (Jin et al, 2014 ). Previous studies have found that PTG may occur in various people who have experienced trauma, such as bereavement (Tan and Andriessen, 2021 ), HIV infection (Ye et al, 2018 ), combat (Marotta-Walters et al, 2015 ), earthquake (Ma et al, 2019 ), and other life-changing events. Studies on patient care indicated that the level of PTG was negatively associated with depressive effect (Siegel et al, 2005 ), emotional distress (Urcuyo et al, 2005 ), and positively associated with quality of life (Xiong et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bereavement support should not only cater to the psychological needs of bereaved young people, but also address social adversity and family psychosocial problems (Berg et al, 2014). As parental grief and mental health problems can affect caregiving and subsequent adaptation in children, it is critical that bereavement support is extended to parents/caregivers to enable continued support of their child's education (Harris, 1991;Lin et al, 2004;Tan & Andriessen, 2021). The role of school psychologists may therefore further extend to linking students and their families to additional community supports.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is known as posttraumatic growth (PTG), defined as the subjective experience of a significantly positive change for an individual following a major life crisis. PTG can follow many different types of traumatic event, such as bereavement (35), combat (36), or cancer (37).…”
Section: Introductionmentioning
confidence: 99%